Surrogate markers in HIV disease. - Peto, T (1996)
The use of surrogate markers in HIV disease is an attractive method of assessing the efficacy of new treatments more quickly than by using clinical end-points. The characteristics of an ideal surrogate marker and the theoretical dangers of extrapolating properties from one class of drug to another are described. These characteristics are compared with the use of the CD4 lymphocyte count, which so far has been the most widely studied. Results from 14 randomized controlled trials of nucleoside analogues are used to compare the comparative changes of CD4 counts with the differential rates of progression to AIDS and differences in survival. There was some correlation between CD4 count changes and development of AIDS, particularly in the short term trials. In contrast, there was little correlation between CD4 counts and overall survival. Comparative studies between clinical end-points and quantitative measures of plasma viraemia have not yet been completed. In conclusion, no surrogate marker has yet been shown to be useful in predicting the efficacy of anti-HIV treatment. Until surrogate markers are validated against the results from long term clinical trials, they should only be used to screen new drugs warranting further study rather than to draw conclusions on the clinical efficacy of new treatments.